2005
DOI: 10.1021/bm049471u
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Structure and Activity Studies of an Enzyme Adsorbed on Spectroscopically Undetectable Particles

Abstract: The structural characteristics and the activity of a hyperthermophilic endoglucanase were investigated upon adsorption. Silica (hydrophilic) and Teflon (hydrophobic) surfaces were selected for the study. The materials were specially designed so that the interaction of the particles with light was negligible, and the enzyme conformation in the adsorbed state was monitored in situ. The adsorption isotherms were determined, and the adsorbed endoglucanase was studied using a number of spectroscopic techniques, enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Previous literature on CD measurements of particulate systems was limited to proteins bound to nanoparticles and encapsulated into biomembrane fragments. [11][12][13] In order to extend the technique for the first time to typical immobilised biocatalyst particles of tens to hundreds of microns in diameter, it was necessary to tackle artefacts associated with particulate sedimentation, differential light scattering and absorption flattening. [10] Particles were kept uniformly dispersed in suspension in the light path using a specially constructed rotating sample cell holder.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature on CD measurements of particulate systems was limited to proteins bound to nanoparticles and encapsulated into biomembrane fragments. [11][12][13] In order to extend the technique for the first time to typical immobilised biocatalyst particles of tens to hundreds of microns in diameter, it was necessary to tackle artefacts associated with particulate sedimentation, differential light scattering and absorption flattening. [10] Particles were kept uniformly dispersed in suspension in the light path using a specially constructed rotating sample cell holder.…”
Section: Resultsmentioning
confidence: 99%
“…Further, surface adsorption can stabilize the structure of proteins and hence improve their resistance to denaturation as compared to dissolved proteins [120][121][122][123].…”
Section: Conformational Changesmentioning
confidence: 99%
“…The pattern of protein stability is necessary to assess the tendency of proteins to be adsorbed on surfaces. The optimal adsorption isotherm equation for describing the interaction between nanoceria and urease is the Sips equation ( Figure 2); this equation is an empirical model for heterogeneous adsorption [Koutsopoulos et al, 2005] where Q e is the adsorption amount normalized by the mass of nanoparticles, Q m is the maximum adsorption capacity, C e is the concentration of the adsorbent in the supernatant at adsorption equilibrium, K S is a constant related to the adsorption energy, and t is a heterogeneity coefficient. The magnitude of t is connected to the factors affecting heterogeneous adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…4. The CD results were analyzed using the K2D2 web server to determine the change in the urease secondary structure from the CD spectra according to the published software (Koutsopoulos et al, 2005). The results showed that the secondary structure of the free urease consists of 84.27 % a-helix and 1.24 % b-sheet, whereas the remainder is random coil.…”
Section: Resultsmentioning
confidence: 99%